Graphene-family nanomaterials assembled with cobalt oxides and cobalt nanoparticles as hybrid supercapacitive electrodes and enzymeless glucose detection platforms. Issue 2 (27th December 2016) - Gupta, Sanju; Carrizosa, Sara B.; McDonald, Benjamin; Jasinski, Jacek; Dimakis, Nicholas
Abstract: Abstract : We report the development of hybrids consisting of supercapacitive graphene oxide (GO), reduced GO (rGO), electrochemically reduced GO (ErGO), multilayer graphene (MLG) decorated with pseudocapacitive nanostructured cobalt oxides (CoO, Co3 O4 ) and nanoparticles (CoNP) via electrodeposition and hydrothermal synthesis facilitating chemically bridged (covalently and electrostatically anchored) interfaces with tunable properties. These hybrid samples showed heterogeneous transport behavior determining diffusion coefficient (4 × 10 −8 –6 × 10 −6 m 2 /s) following CoO/MLG < Co3 O4 /MLG < Co3 O4 /rGOHT < CoO/ErGO, CoNP/MLG and delivering the maximum specific capacitance >550 F/g for Co3 O4 /ErGO and Co3 O4 /MLG. We found an ultrahigh sensitivity of 4.57 mA/(mM cm 2 ) and excellent limit of glucose detection <50 nM following Co3 O4 /rGOHT < CoO/ErGO < CoNP/MLG < Co3 O4 /MLG. These findings are due to open pore network and topologically multiplexed conductive pathways provided by graphene nanoscaffolds to ensure rapid charge transfer and ion conduction. Density functional theory determined density of states in the vicinity of Fermi level in-turn providing contribution toward electroactivity due to orbital re-hybridization.